Long-term Variation of Sensible Heat Flux over the Qinghai-Xizang Plateau from 1984 to 2020 - Runzhi LEI; Ye YU; Guobin ZHOU; Jianglin LI; Yanfei LIU (Gaoyuan qixiang)
Sensible heat flux （SH） is one of the main physical quantities characterizing the thermal effect of the Qinghai-Xizang Plateau， which is affected by the surface temperature， air temperature， heat exchange coefficient and wind speed.However， different heat exchange coefficient （CH）calculation methods give SH with different values.To solve this， in this study， three CH calculation methods are used to calculate the SH using the conventional meteorological observation data from 89 stations on the Qinghai-Xizang Plateau for 1984 -2020.The SHs obtained by different CH algorithms are verified using in situ SH observations from 5 flux stations.The results indicate that the SH calculated by Chen and Weng （1984） （CH-CW） scheme is the best in terms of the smallest bias between the caculations and observaitons.The long-term trend of SH calculated with CH-CW scheme and the characteristics and causes of the long-term change over the Qinghai-Xizang Plateau are analyzed using PLFIM piecewise linear fitting model.The results show that the trend of the annual SH over the Qinghai-Xizang Plateau have turning points at 1999 and 2009.The SH decreased from 1984 to 1999， increased significantly from 1999 to 2009， and showed a weak downward trend from 2009 to 2020.The turning points of SH trend in summer are 2000 and 2010， respectively.The turning points of SH trend in other seasons are the same as the annual SH.The overall trend of SH in spring， summer and autumn is consistent with the annual trend， characterized by "weakened - strengthened - weakened".The SH in winter continued to increase from 2009 to 2020， but with a much weaker trend compared with that from 1999 to 2009.Attribution analysis shows that the decrease of annual SH from 1984 to 1999 is mainly attributed to the decrease of wind speed； the increase of annual SH from 1999 to 2009 was mainly due to the increase of surface-air temperature difference caused by the significant increase of surface temperature， and less to the slow down of wind speed increase.From 2009 to 2020， the significant increase of wind speed led to a decrease of CH， and the relative faster increase of air temperature compared to the increase of the surface temperature lead to a decrease in the surface-air temperature difference， both of which contributed to the decrease of the annual average SH during this period， with the negative contribution from the surface-air temperature difference much lager than that from the CH change.